Blended Learning in the Spotlight of Educational Management - A Scientometric Analysis - Jardas Antonić, Jelena; Srok, Antonija; Vretenar, Nenad (Journal of Information and Organizational Sciences, 2024)
The mass adoption of ICT for online delivery of education due to the COVID-19 pandemic has brought many opportunities but also challenges for the education sector. In this paper, we conducted a scientometric analysis to provide insights into research trends and present bibliometric indicators of 5810 publications on blended learning to contribute to the knowledge base on the use of ICT in education management, during and after the COVID-19 pandemic, from 2020 to 2023. The number of citations and publications increased rapidly. Content analysis of the publications and keyword analysis revealed important and emerging topics such as the challenges and experiences of students, teachers and institutions with blended learning, especially in higher education, from implementation and use to digital literacy, attitudes, performance, self-regulation and learning outcomes. The main journals focused on the use of technology in education and health education. Blended learning has likely moved beyond the pandemic and has become an integral part of management in educational organizations.